2007
DOI: 10.1130/b26019.1
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene sediment accumulation on the northern California shelf: Oceanic, fluvial, and anthropogenic influences

Abstract: The late Holocene sedimentary record of the northern California continental shelf archives the combined infl uences of fl uvial and oceanic mechanisms of land to ocean sediment fl ux, and provides perspective on the cumulative impacts of major fl oods and land-use change in the drainage basin during historical time. Piston cores collected on the shelf (50−150 m water depths) off the Eel and Klamath Rivers were analyzed to identify lithologies indicative of depositional processes over the past 5 k.y., and dated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 72 publications
(87 reference statements)
1
29
0
Order By: Relevance
“…1). Average sedimentation rates are nonetheless approximated by interpolation of ln( 210 Pb xs ) versus depth to be 1.1 and 0.6 cm yr -1 over the length of GGC5 and MC36, respectively, in broad agreement with other estimates for the mid-shelf depocenter (Leithold et al, 2005;Sommer fi eld and Nittrouer, 1999;Sommerfi eld and Wheatcroft, 2007). As gravity coring usually displaces several centimeters of surfi cial sediments, the depth scale for GGC5 was linked to the seafl oor via comparison of its 210 Pb xs and 137 Cs activities to those of MC36.…”
Section: Resultsmentioning
confidence: 62%
“…1). Average sedimentation rates are nonetheless approximated by interpolation of ln( 210 Pb xs ) versus depth to be 1.1 and 0.6 cm yr -1 over the length of GGC5 and MC36, respectively, in broad agreement with other estimates for the mid-shelf depocenter (Leithold et al, 2005;Sommer fi eld and Nittrouer, 1999;Sommerfi eld and Wheatcroft, 2007). As gravity coring usually displaces several centimeters of surfi cial sediments, the depth scale for GGC5 was linked to the seafl oor via comparison of its 210 Pb xs and 137 Cs activities to those of MC36.…”
Section: Resultsmentioning
confidence: 62%
“…Characteristics of deep-time sediment production and 1176 transfer areas can be interpreted by employing provenance tools, detrital mineral analysis, 1177 or application of empirical relationships based on modern systems, and tested with 1178 conceptual, analytical, and numerical models. Sommerfield and Wheatcroft, 2007). 1199…”
Section: Discussion and Research Directions 1141mentioning
confidence: 99%
“…The character of that signal and to what extent a signal is 1144 preserved in sedimentary records are dependent on the magnitude and frequency of the 1145 initial forcing (Fig. 8), on their initial recording or destruction (Wheatcroft et al, 2007), The investigation of signal propagation requires a systems approach, which is 1163 provided by the sediment-routing system, or source-to-sink, framework (Allen, 2008a) 1164 (Fig. 1).…”
Section: Discussion and Research Directions 1141mentioning
confidence: 99%
“…There is some input of finer grained sediment from plumes and nepheloid layers; although it used to be considered that these volumes were comparatively small, recent detailed sediment budgets have suggested that they may be substantial. Thus, for example, Sommerfield and Wheatcroft (2007) found that 20% of terrigenous sediment delivered to the ocean from the Eel River in California accumulates on the outer shelf, although note that this is a narrow shelf environment (c. 12-17 km). A small number of outer-shelf environments are affected by the effects of ocean currents; examples include the outer Saharan shelf, the Middle Atlantic Bight and the southeastern African shelf.…”
Section: Sediment Cascades On Ocean-dominated Shelf Environmentsmentioning
confidence: 99%